2DOOR REFRIGERATOR NEW PRODUCT DEVELOPMENT ANALYSIS BY USING QFD METHOD: A CASE STUDY REFRIGERATOR PRODUCT IN INDONESIA - Yulianto, Yulianto; Purba, Humiras Hardi; Purowenang, Candra (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2020)
This study aims to find out the features of a 2-door refrigerator product that suitable the needs and desires of consumers at this era. The need and ever-growing desire for refrigerator products is not just to condition food or drinks or other goods so that the condition remains fresh or controlled at a certain temperature. The method used is Quality Function Deployment (QFD) by capturing customer voice (VOC). With this method the consumer voice obtained is then translated into product technical requirement in the development of new products. In this study the products studied were 2-door refrigerator products types that were suitable for the needs of consumers with a small number of families with consumer routines activities. The results of the study it was found that, there are 3 big points of the 2-door refrigerator products that consumers want that rapid freezing time, low prices, and low electricity consumption. To achieve this requirement, the fabrication company carries out air flow type modification, efficiency production cost, material usage and use of special components to get efficient energy products.